The Day Israel Attacked America | Special Series - Al Jazeera English (2014)
1,318,463 views • Nov 3, 2014 • Al Jazeera investigates the shocking truth behind a deadly Israeli attack on a US naval vessel. Subscribe to our channel http://bit.ly/AJSubscribe Follow us on Twitter https://twitter.com/AJEnglish Find us on Facebook https://www.facebook.com/aljazeera Check out our website:http://www.aljazeera.com/ Show less Show more